Cocreation or Collusion: The Dark Side of Consumer Narrative in Qualitative Health Research. (October 2018) - Pascal, Jan; Sagan, Olivia
Health, mental health, and social care policy are dominated by the imperative of employing person-centered approaches. Such involvement of the "consumer" is generally claimed to provide a counter-narrative to the psychiatric and medical paradigm of illness. Taking a critical and reflexive standpoint, we find ourselves asking: Is there a dark side to employing person-centered approaches and potential loss and risk to participants themselves? To explore these questions further, we undertook a condensed critique of the current mental health, health, and social care policy arena. We then move to methodological concerns about ways in which person-centered research, including our own, can inadvertently reproduce the neoliberalist agenda. To conclude, we offer our own lived experiences as a cautionary tale. We also posit that a post-Foucauldian governmentality framework can assist researchers to avoid contributing to the very problems we wish to resolve.